1995
DOI: 10.1080/10292389509380516
|View full text |Cite
|
Sign up to set email alerts
|

Investigating age‐dependency of species extinction rates using dynamic survivorship analysis

Abstract: Survivorship curves with taxon lifespans normalised to variations in the real-time extinction rate (the 'Corrected Survivorship Score' technique) are plotted for various fossil groups. Of five groups tested at the 'species level' (strictly speaking, Linnean morphospecies), only the calcareous nannoplankton are found to have had a constant extinction probability with respect to morphospecies age. The planktonic foraminifer, trilobite, conodont and graptolite data all show a significant agedependent effect (conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 35 publications
4
44
1
Order By: Relevance
“…The planktic foraminifera, in contrast, generally show taxon age to be positively related to extinction [β > 1 (4,24,48,49)]; Doran et al (49) found, for the planktic foraminifera, significant positive age dependency of extinction in the long recovery periods following mass extinctions. The graptolites seem to show features of both these patterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The planktic foraminifera, in contrast, generally show taxon age to be positively related to extinction [β > 1 (4,24,48,49)]; Doran et al (49) found, for the planktic foraminifera, significant positive age dependency of extinction in the long recovery periods following mass extinctions. The graptolites seem to show features of both these patterns.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether the positive dependence of extinction risk on taxon age during the LOME indicates that a novel extinction mechanism was operating during this event or whether it represents simply an extreme expression of the processes operating during other severe extinction episodes. One possible mechanism for the high β-values is that when environmental change is severe and rapid enough, old species that were adapted to a previous environment become maladapted in the new environment, compared with newly evolving species, and are selectively removed (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this formula, Pearson described the variation in extinction rates with respect to the longevity of taxon or age dependency of extinction rates. This was contrasted with variation in extinction rates in real time or time dependency (Pearson, 1995). The CSS normalized timedependent information to leave age-dependent trends.…”
Section: Introductionmentioning
confidence: 99%